Preparation and Characterization of Chitosan-Humic Acid-Zerovalent Iron Nanocomposite for Nitrate Reduction in Water. (5th September 2016) - Akinremi, Caroline Avosuahi; Omosun, Nikechukwu Nike; Adewuyi, Sheriff; Azeez, Jamiu Oladipupo; Olanrewaju, Sanyaolu Nurudeen
Abstract : A new zerovalent iron chitosan-humic acid nanocomposite was prepared and tested for nitrate ion reduction in water. Humic acid was used for intramolecular cross-linking of the chitosan linear chains to increase the active sites on the chitosan biopolymer and then further used as a stabilizer to synthesize zerovalent iron nanoparticles by the reduction of iron (II) chloride with sodium borohydride. Characterization of the products was carried out using infrared spectroscopy, scanning electron microscope, energy dispersive X-ray, and X-ray diffractometer. Batch experiments were conducted for the reduction of nitrate in water using different concentrations of the products in different concentrations of nitrate ion and at different contact time. The adsorption equilibrium data for the nitrate solution gave a favorable adsorption according to the Langmuir equation. Varying the nanocomposite-to-nitrate ion ratio generally led to faster nitrate reduction, with the pseudofirst-order rate constant for the adsorption increasing with increase in nanocomposite-to-nitrate ion ratio. Nitrate removal efficiency of zerovalent iron chitosan-humic acid nanocomposite was further confirmed using real water samples obtained from drainage waste and river with an initial nitrate concentration of18.00 ± 0.01 and12.00 ± 0.12  ppm, respectively. The reduction of nitrate in water using the nanocomposite was concluded to be highly effective.